Investigation of the combined effect of variable inlet guide vane drift, fouling, and inlet air cooling on gas turbine performance - Hashmi, M.B. (2019)
Variable geometry gas turbines are susceptible to various malfunctions and performance deterioration phenomena, such as variable inlet guide vane (VIGV) drift, compressor fouling, and high inlet air temperatures.